2022
DOI: 10.3390/biology11030452
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of ADC First-Order Histogram Features for the Prediction of Metachronous Metastases in Rectal Cancer: A Preliminary Study

Abstract: This study aims the ability of first-order histogram-based features, derived from ADC maps, to predict the occurrence of metachronous metastases (MM) in rectal cancer. A total of 52 patients with pathologically confirmed rectal adenocarcinoma were retrospectively enrolled and divided into two groups: patients who developed metachronous metastases (n = 15) and patients without metachronous metastases (n = 37). We extracted 17 first-order (FO) histogram-based features from the pretreatment ADC maps. Student’s t-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
2
1
Order By: Relevance
“…In our study, ADC 90 values of both SS-EPI and RS-EPI in group B were lower than those in group A. A possible explanation for this finding could be that more aggressive tumors may contain many invisible cystic and necrotic components 30 . However, Zhang et al 6 reported that ADC min had the highest value in distinguishing normal-sized LNM in cervical cancer.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In our study, ADC 90 values of both SS-EPI and RS-EPI in group B were lower than those in group A. A possible explanation for this finding could be that more aggressive tumors may contain many invisible cystic and necrotic components 30 . However, Zhang et al 6 reported that ADC min had the highest value in distinguishing normal-sized LNM in cervical cancer.…”
Section: Discussioncontrasting
confidence: 50%
“…A possible explanation for this finding could be that more aggressive tumors may contain many invisible cystic and necrotic components. 30 However, Zhang et al 6 reported that ADC min had the highest value in distinguishing normal-sized LNM in cervical cancer. Although ADC min theoretically best represents the most aggressive component of a tumor, it is more susceptible to noise, artifacts, and adjacent structures.…”
Section: Discussionmentioning
confidence: 99%
“…While the first order overall describes the distribution of voxel intensity within the image region through commonly used and basic metrics, the histogram feature specifically describe the frequency distribution of voxel intensity. Histogram features on ADC maps have been shown to yield significant predictive performance in a multitude of studies-such as in Boca Petresc et al [43], Lenoir et al [27], Rodrigues et al [44], and Fujima et al [45]-and, as such, it is intuitive that they would reveal more about microstructural alterations in the primary lesion in this current study.…”
Section: Adc Mapsmentioning
confidence: 61%